Use of Standardized Patient Simulations to Assess Impact of Motivational Interviewing Training on Social-Emotional Development - Suzanne Galal; Deepti Vyas; John Mayberry; Edward L. Rogan; Shivani Patel; Sara Ruda (MDPI AG, 2018)
The objective of this study was to assess the impact of motivational interviewing (MI) training on students’ social–emotional development. Two simulations using standardized patients (SP) were conducted within a smoking cessation module. Students first completed a 4 h self-study module focused on smoking cessation tools and general counseling techniques. Faculty then administered a 15-item rubric focused on students’ self-assessment of their verbal/non-verbal communication, social–emotional competence and MI skills. Students then participated in a smoking cessation counseling session with an SP. SPs used the same rubric to assess student performance. Teaching assistants (TAs) observed and assessed the students using the same rubric and an additional 22 items related to clinical skills. TAs and SPs then provided feedback on areas of improvement. The following week, students first completed a 3 h self-study module on MI then participated in a different smoking cessation scenario. After completion, the 15-item self-assessment rubric was administered. There was a significant improvement in TA assessed student performance with an average score improvement of 8% (pre-intervention score = 67%; post-intervention mean = 75%). Students had dramatic gains in their self-assessment with their scores rising by an average of 22%. Using MI techniques can improve students’ self-assessed and perceived social–emotional competency.